Enhanced performance of nitrogen-doped carbon nanotube membrane-based filtration cathode microbial fuel cell. (1st September 2016) - Zuo, Kuichang; Liu, Han; Zhang, Qiaoying; Liang, Peng; Vecitis, Chad D.; Huang, Xia
Abstract: In this study, nitrogen-doped carbon nanotube (N-CNT) membrane compared with Pt-coated CNT (Pt-CNT) membrane and pristine CNT membrane were utilized as air cathode as well as filtration material of microbial fuel cells (MFCs). The MFCs were continuously operated for 39 days to investigate their power generation, organics removal, proton transfer, and fouling behavior under various influent concentrations and hydraulic retention times (HRTs). During operation, the N-CNT filtration MFC achieved the best effluent quality and power generation, with efficient removal of total organic carbon (TOC) (95.2%) and NH4 + -N (97.7%), and maximum power density and current density of 408 mW/m 2 and 2.36 A/m 2 respectively. The excellent performance of the N-CNT MFC was mainly attributed to its special morphology and rich N-functional groups. The N-CNT membrane has a nanotube diameter of 37 ± 4 nm, pore size of 95 ± 33 nm, and porosity of 79.9%, which was even better than traditional microfiltration membrane as a filtration material for pollutant removal. The high nitrogen content (2.12 at%) and high specific surface area (93.5 m 2 /g) due to its network structure also enhanced O2 reduction. In addition to the excellent performance of N-CNT cathode, the filtration operation enhanced cathode O2 reduction by increasing mass transfer in cathode micro-pore and improving proton transfer with water flowing from anode to cathode. Moreover, a separate experiment also demonstrated that the cathode fouling could be mitigated under high current operation.